Assessment of Knowledge and Practice of Food Safety and Hygiene Among Food Vendors in Selected Primary Schools Within Sokoto Metropolis - Usman Babadoko; Muhammad Salim Isah; Zulkiflu Musa Argungu; Nuraddeen Abubakar Argungu; Nasir Muhammad (American Journal of Medicine and Health Care, 2026)
Foodborne diseases represent a significant public health challenge in developing countries, with contaminated food from unhygienic food vendors being a major source of morbidity and mortality, particularly among vulnerable populations, including schoolchildren. Food hygiene practices among vendors serving primary school children require a comprehensive assessment to guide health promotion and policy interventions. This study assessed the knowledge, practices, and improvement strategies for food safety and hygiene among food vendors operating in selected primary schools within Sokoto Metropolis. A descriptive cross-sectional study was conducted with 100 food vendors selected through multi-staged sampling from 20 primary schools across three local government areas in Sokoto Metropolis. Data were collected using a structured questionnaire comprising demographic information, knowledge assessment, practice evaluation, and improvement strategies. Descriptive statistics, including frequency distributions and percentages, were used for data analysis. Seventy-two per cent of food vendors demonstrated knowledge of food safety and hygiene principles. The majority engaged in good food safety practices, with 88% using clean utensils when serving food, 82% washing vegetables thoroughly before preparation, and 80% maintaining clean school premises. Key improvement strategies identified included attending food safety training programs (14%), avoiding cross-contamination (12%), and maintaining appropriate food storage temperatures (12%). Food vendors in primary schools demonstrated adequate knowledge and reasonably good food safety practices. However, systematic food safety training programs, regular environmental health inspections, and the provision of adequate facilities for handwashing and waste disposal are essential for sustaining and improving food hygiene standards. School health programs should be strengthened through collaboration between educational and health authorities.